The effect of biological factors on Fusarium oxysporum inhibition causing Fusarium wilt disease on cowpea ( _Vigna unguiculata_ ) - Zainab Asaad Jabr; Alaa Oudah Manea (University of Thi-Qar Journal of agricultural research, 2024)
This study was conducted for the agricultural season 2023-2024 with the aim of evaluating the efficiency of bio agent of Bacillus cereus, Trichoderma Longibrachiatum and Saccharomyces cerevisiae on Cowpea plants infected with Fusarium wilt disease in pots. Three isolates R2, R3 and R7 of Fusarium oxysporum were isolated from the roots of Cowpea plants that showed symptoms of wilt. The isolated fungi were diagnosed morphologically and partially. The results of molecular diagnosis of the fungi showed 100% matching of the isolates. Pathogenicity tests were conducted on cowpea seeds in the laboratory using Petri dishes containing W.A medium as a pathogen for cowpea plants, as the germination percentage of cowpea seeds for all isolates reached 76.66, 66.66 and 63.66% compared to the control treatment which reached 100%. The results of the pot experiment showed that there were no significant differences in the infection severity by the pathogenic fungus in the three isolates, as R2 reached 82.00, R3 82.00 and R7 87.33% respectively compared to the control treatment which reached 0.00%. The results of the pot experiment indicated the effect of bio agent in increasing some plant growth indicators and reducing the infection severity which reached 0.00% in the T. Longibrachiatum, B. cereus and S. cerevisiae treatments. It was also noted from the results that the highest germination rate of cowpea seeds was in the yeast S. cerevisiae treatment, which reached 96.00% compared to the control treatment, which reached 100%. The results of chlorophyll estimation indicated that the treatment of the biological fungus T. Longibrachiatum and the yeast S. cerevisiae was similar to the control treatment, which reached 0.82 mg/g¯¹.